Clinical indication-based diagnostic reference levels for paediatric head computed tomography examinations in Kano Metropolis, northwestern Nigeria. Issue 2 (May 2021) - Joseph Zira, D.; Haruna Yahaya, T.; Umar, M.S.; Nkubli B, F.; Chukwuemeka, N.C.; Sidi, M.; Emmanuel, R.; Ibrahim, F.Z.; Laushugno, S.S.; Ogenyi, A.P.
Abstract: Introduction: Paediatric patients are recognised to be at higher risk of developing radiation-induced cancer than adults because of rapidly growing organs and tissues which are vulnerable to cellular damage. The aim of the study was to determine indication based Diagnostic Reference Levels (DRLCI ) for paediatric head computed tomography (CT) examinations within Kano metropolis, Nigeria. Methods: CT dose index (CTDIvol ), dose length product (DLP) and other scan parameters were recorded for 113 paediatric undergoing CT head examinations. Different clinical indications were recorded and categorised in addition to patient age. Third quartile values (75th percentile) of the median dose were considered as DRLCI . Analysis of Variance (ANOVA) was used to test for differences between DRLCI, for different age groups, and variations among institutions. The Statistical Package for Social Sciences version 23.0 was used for analysis. Statistical significance was set at p < 0.05. Results: DRLCI for Hydrocephalus for <5 years and 5–10 years was 28.10 mGy and 28.11 mGy with DLP of 1623.20 mGy cm and 1623.21 mGy cm, respectively. The 11–15 year group recorded 29.10 mGy and 1625.20 mGy cm. Indications of haemorrhage/trauma and post-seizure imaging all had same values for <5 years and 5–10 years (28.10 mGy and 1623.20 mGy cm) while the 11 to 15-year group recorded 39.60 mGy and 1626 mGy cm. Intracranial Space Occupying lesion had the same DRLCI value for < 5years and 5–10 years (29.0 mGy and 1600 mGy cm, respectively) the 11 to 15-year group recorded values of 46.20 mGy and 1663.4 mGy cm. There was no statistically significant difference between DRLCI for <5 years and 5 to 10-year age groups (p = 0.199), while different centres showed some statistically significant relationships (p = 0.02). Conclusion: The study noted dose differences between age groups less than 10 years and above ten years, there were some statistically significant relationship with DRLCI . Dose optimisation techniques for paediatric examinations together with selection of the right protocol for paediatric head CT are necessary. Implications for practice: The study has provided DRLCI for paediatric head CT examinations. These values can be used for future comparisons and as a potential dose optimisation tool. Such data can also guide radiographers when selecting appropriate parameters for indication-based CT examination to help achieve a low dose with acceptable image quality.